Effect of salt loading on baroreflex sensitivity in reduced renal mass hypertension. (3rd October 2017) - Özaykan, Besim; Taskin, Eylem; Magemizoğlu, Ali
ABSTRACT: Background : High dietary salt, as well as renal mass reduction, is known to decrease baroreflex sensitivity in rats. However, the effect of high salt intake on baroreflex sensitivity is unknown in reduced renal mass (RRM) hypertension; therefore, the aim of this study was to investigate the effects of salt loading on arterial baroreflex sensitivity and mean arterial pressure (MAP) in RRM hypertension. Methods : Both RRM and sham-operated control (SO) rats were loaded with 0.25 or 0.5% NaCl for five weeks. Plasma Na +, K +, and creatinine levels were measured, and baroreflex sensitivity was evaluated before and after β1 blockade. In addition, cardiac vagal tone and intrinsic heart rate (IHR) were measured. RESULTS: RRM decreased full baroreflex sensitivity of the tachycardic response under 0.5% NaCl loading and the parasympathetic bradycardic response under 0% NaCl loading. The NaCl loading did not affect the severity of RRM hypertension. Cardiac vagal tone and IHR decreased in RRM rats versus SO controls under all NaCl loading conditions. RRM decreased plasma K + under 0% NaCl loading and increased plasma Na + under 0.5% NaCl loading. High (0.5%) NaCl loading decreased IHR and increased plasma creatinine and left ventricular weight in RRM rats. CONCLUSIONS: RRM in combination with 0.5% NaCl loading led to a decrease in the sensitivity of full baroreflex and of the parasympathetic component of baroreflex. Changes in plasma Na + and K + levels, due to NaCl loading, may have contributed to the decrease in baroreflex sensitivities and IHR but had no effect upon MAP in RRM rats.